A Glimpse of the Interaction between N-Nitrosamines and HPV E5 in Rodent Cell Transformation - Liu, Hongwei; Li, Shuying; Li, Jintao (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: A few epidemiologic surveys and experimental studies observed the synergistic carcinogenic effect of nitrosamines and High-Risk Human Papillomavirus (HPV) in partial digestive tract cancers. They mainly focused on the co-carcinogenesis of HPV E6 and E7 in cancer development. HPV E5 plays an important role in early-stage cancer but has limited capacity as an independent carcinogen. Objective: To investigate whether nitrosamines enhance the carcinogenesis of E5, a rapid in vitro rodent cell transformation assay was established. Materials and Methods: We have successfully established BALB/c 3T3-E5 cells expressing HPV16 E5 using a lentivirus vector. Six foodborne N-nitroso Compounds (NOCs) are selected to induce malignant cell transformation. Results: We have screened two compounds with strong transformation capability, N-nitrosodimethylamine and N-nitrosodiethylamine alone. The combined action of NOCs and E5 is highly efficient, with more transformed foci than a single NOC or E5 oncoprotein, and the synergistic effect becomes more evident with increasing concentrations of NOCs, especially N-nitrosodipropylamine. Furthermore, we also confirm the working concentration range of 0.05-0.1 ng/mL of NOCs to meet the demands for cell viability in carcinogenicity tests. Conclusion: In conclusion, we provide cell models for studying the interaction mechanism of HPV16 E5 and NOCs, as well as assessing preventive or therapeutic candidates for HPV-positive tumors in the future.
Keywords: Human Papillomavirus16; E5 oncoprotein; N-nitrosamines; BALB/c 3T3 cell; Synergy; effect; Carcinogenicity